Outcomes of Emergency Laparotomy in Pregnant and Postpartum Patients - Naseem Saba, Muhammad Hamayun Khan, Neelam Mehsood, Sobia Rashid, Momina Ali Khan, Momin Ali Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Emergency laparotomy in pregnant and postpartum patients is a rare but critical intervention, associated with high maternal and fetal morbidity and mortality. Obstetric and non-obstetric emergencies, including uterine rupture, postpartum hemorrhage, intestinal obstruction, and perforation, often necessitate urgent surgical exploration. Understanding local patterns of indications and outcomes is essential for improving clinical protocols and multidisciplinary care. Objective: To assess maternal and fetal outcomes following emergency laparotomy in pregnant and postpartum patients and identify factors associated with adverse clinical outcomes at a tertiary care hospital in Peshawar. Methods: This hospital-based observational study included all pregnant women and postpartum patients (up to 42 days post-delivery) undergoing emergency laparotomy over a defined study period. Demographic, clinical, operative, and postoperative data were collected using a structured proforma. Maternal outcomes included ICU admission, blood transfusion, surgical site infection, re-exploration, and mortality. Fetal outcomes assessed among pregnant patients included live birth, preterm delivery, fetal distress, and intrauterine fetal demise. Statistical analysis was performed using SPSS, with p-values <0.05 considered significant. Results: A total of 120 patients were analyzed (74 pregnant, 46 postpartum). Postpartum patients had significantly higher ICU admission (47.8% vs 27.0%, p=0.02), blood transfusion (82.6% vs 54.1%, p=0.001), and maternal mortality (13.0% vs 2.7%, p=0.04) compared with pregnant patients. Live birth was achieved in 70.3% of pregnant patients, with preterm delivery in 18.9% and fetal distress in 8.1%. Obstetric indications predominated in both groups. Conclusion: Emergency laparotomy in pregnant and postpartum patients carries substantial maternal and fetal risks, particularly in the postpartum period. Early recognition, timely surgical intervention, and multidisciplinary management are crucial to optimize outcomes. Keywords: Emergency laparotomy, pregnancy, postpartum, maternal outcomes.